MAKNA SIMBOLIK LIRIK LAGU DALAM ALBUM RUBIK OLEH DERE DAN KEPOPULERAN LAGUNYA DI KALANGAN MAHASISWA SASTRA INDONESIA STAMBUK 2022 USU:SEMIOTIKA CHARLES SANDERS PEIRCE - Sopia Lorena Br Karo Lorena; Nurhayati Harahap; Emma Marsella (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Song lyrics as part of literary works in popular music do not only function as entertainment but also contain a system of signs that represent human experiences and realities. The album Rubik by Dere is interesting to study because it presents poetic lyrics with implicit meanings and has gained attention among university students. This study aims to describe the symbolic meanings in the lyrics of the Rubik album and to examine students’ perceptions of its popularity. This research employs a mixed-methods approach, combining qualitative and quantitative methods. The qualitative data in the form of song lyrics are analyzed using the semiotic theory of Charles Sanders Peirce through the classification of signs into icons, indexes, and symbols, with a focus on symbols. The quantitative data are collected through a Likert-scale questionnaire distributed to Indonesian Literature students of Universitas Sumatera Utara, class of 2022, and analyzed using descriptive statistics with the assistance of SPSS. The results show that symbolic meanings in the lyrics are dominated by symbols representing inner experiences, social relations, and reflections on life. In addition, students’ perceptions indicate a positive level of popularity. Therefore, the Rubik album demonstrates both rich symbolic meaning and strong appeal among students.